Female haircare purchase? Choices and Preferences- Study of South African Consumer - Ankit Katrodia; ogone asitile (AMAR (Andalas Management Review), 2025)
This study focuses on women's purchase intentions for hair care products. Purchase intentions influence the possibility of purchasing a product or service and lead to real buying behaviour and Customer’s purchase intention of haircare products depends on, among other factors: quality and value, satisfaction, price sensitivity, social influence and packaging which might directly influence behavioural intentions.